Answer:
x^2 + 18x + 76 + 5 = 0 + 5
Step-by-step explanation:
The first step is to determine the constant that is needed to be able to write the expression in the desired form. That constant is the square of half the x-term coefficient: (18/2)^2 = 9^2 = 81.
The constant that is present is 76, which is 5 fewer than the needed constant, so the "first step" is to add 5 to both sides of the equation:
x^2 + 18x + 76 + 5 = 0 + 5
Then the next step would be to write the left side as a square:
(x +9)^2 = 5 . . . . . . . p = -9; q= 5
3* (a + 1,5) = - 1,5 [:3
a + 1.5 = - 0,5
a = - 0,5 - 1.5 = -2
Answer:
his dad was cutting the grass for 1 hour and 4 minutes i hope this helps
Step-by-step explanation:
Answer:
= 3b/4
Step-by-step explanation:
= b . 4/12 + b . 3/12 + b . 2/12
Apply the fraction rule: a/c + b/c = a + b/c
= b . 4 + b . 3 + b . 2/12
= 4b + 3b + 2b/12
Add similar elements: 4b + 3b + 2b = 9b
= 9b/12
Cancel 9b/12: 3b/4
= 3b/4
Hi,
John haves 99 stickers. If Sally gave him 36 more that means john haves 99 + 36 = 135 more stickers than Sally.
Hope this helps.
r3t40